Gender differences in hypertension. Issue 3 (May 2018) - Reckelhoff, Jane F.
Abstract : Purpose of review: The review is a short discussion of sex/gender differences in blood pressure control with a focus on gender differences in hypertension awareness, prevalence, and treatment, the new American College of Cardiology/American Heart Association Guidelines, and recent discoveries in animal models and humans on mechanisms responsible for sex/gender differences in hypertension. Recent findings: Hypertension awareness is greater in women than men, the prevalence of hypertension is higher in men than women until after menopause, and although the American College of Cardiology/American Heart Association Guidelines recommend similar treatment for men and women, this is not currently the case in practice. New studies into mechanisms responsible for sex/gender differences in hypertension include the role of the kidneys, the renin–angiotensin system, relaxin, and developmental programming. Summary: Specific guidelines for hypertension treatment in women and men have yet to be developed. However, numerous animal and human studies have shown differences in the mechanisms responsible for blood pressure control between the sexes. Thus more research into the sex/gender differences in mechanisms responsible for hypertension are needed to determine the best treatment options that will reduce the risk of hypertension and subsequent cardiovascular diseases in both genders.